2021
DOI: 10.1108/ajeb-02-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Why does Shariah governance framework important for Islamic banks?

Abstract: Purpose The purpose of this paper is to explore the question “Why does Shariah Governance Framework (SGF) important for Islamic banks?” Design/methodology/approach A semi-structured face-to-face personal interview is used to accomplish the research objectives. This study has collected data from the concerned bodies related to Shariah Governance (SG) from the central bank and Islamic banks of Bangladesh. Findings This study states SG as a process of confirming Shariah compliance in the overall functions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
0
27
0
1
Order By: Relevance
“…Several studies have shown Shariah corporate governance's urgency in preventing fraud (Ghoniyah and Hartono, 2020; Yusmansyah et al , 2020; Alam et al , 2021). Shariah compliance and profit distribution management are two key factors in reducing fraud in Islamic banks (Ghoniyah, Mutamimah and Amilahaq, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Several studies have shown Shariah corporate governance's urgency in preventing fraud (Ghoniyah and Hartono, 2020; Yusmansyah et al , 2020; Alam et al , 2021). Shariah compliance and profit distribution management are two key factors in reducing fraud in Islamic banks (Ghoniyah, Mutamimah and Amilahaq, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…“SG as a process of confirming Shariah compliance in the overall functions of the Islamic banks” (Alam et al , 2021a, 2021b, p. 158). In addition, Alam et al (2021a, 2021b, p. 158) stated that “SGF is important for Islamic banks to implement Shariah principles, confirm Shariah compliance and monitor the functions of the banks.” However, the SGF is diversified and varied from county to country, framework to framework because of the socio-cultural and political situations and circumstances (Hassan et al , 2011). The world SG practices are seen in three types practiced by Islamic finance such as centralized SGF, decentralized or laissez-faire and hybrid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To solve these problems, most of the researchers put the strength on the development of homogeneous SG guidelines and suggested setting up a centralized Shariah supervisory board (CSSB) within the central bank (Alam and Miah, 2021; Alam et al , 2021a, 2021b; Alam et al , 2020a, 2020b, 2020c, 2020d; Alam et al , 2019; Noman et al , 2017; Perves, 2015; Ullah, 2014; Ahmad et al , 2014). Moreover, several studies have highlighted the benefits of homogeneous guidelines or a CSGF for the Islamic banking industry in Bangladesh rather than providing a structure of CSGF.…”
Section: Introductionmentioning
confidence: 99%
“…The success of an organization, particularly Islamic banks, is subject to the preparedness of the administration to endorse and essentially enact Islamic principles in the operation of the organization. Equally, [43] emphasized the role of the BOD in guaranteeing the adequate implementation of the SG. [61] examined the significance of SG of the Islamic banks and emphasized similarities between traditional banks and Islamic banks.…”
Section: Board Of Directorsmentioning
confidence: 99%